Synthesis of enantiopure aminonaphthol derivatives under conventional/ultrasonic technique and their ring-closure reaction - Pelit, Emel; Turgut, Zuhal (ELSEVIER SCIENCE BV, 2016)
New optically active aminoalkylnaphthols were obtained by condensation of 2-naphthol, substituted aromatic and heteroaromatic aldehydes and (R)-(+)-1-phenylethylamine or (S)-(-)-1-phenylethylamine under conventional methods and ultrasonic irradiation. The enantiopure aminoalkylnaphthol derivatives were converted in ring-closure reaction with formaldehyde to the corresponding naphthoxazine derivatives. (C) 2014 King Saud University. Production and hosting by Elsevier B.V. All rights reserved.
Keywords: Mannich reaction; Ultrasonic irradiation; Aminoalkylnaphthol compound; One pot reaction; CATALYTIC ENANTIOSELECTIVE ADDITION; RICH AROMATIC-COMPOUNDS; ONE-POT SYNTHESIS; ULTRASOUND IRRADIATION; BETTI BASE; STEREOSELECTIVE SYNTHESIS; ARYL ALDEHYDES; DIETHYLZINC; AMINOALKYLATION; DIALKYLZINCS; Chemistry